Remembering past emotions: How emotion expressions are linked to memory reappraisal - Deniece S. Nazareth; Khiet P. Truong; Dirk Heylen; Peter Kok; Gerben J. Westerhof (PLoS ONE, 2025)
This paper examined how older adults experience the past and present valence of emotional memories and its relation to their multimodal expressions. As older adults can become more biased towards positive emotions and minimize negative emotions, a valence difference in the reappraisal of memories can exist. A study was conducted with older adults (N = 17) who self-reported their past and present valence of emotional memories. Data were collected between July and November 2018. Using automatic recognition technology, facial, acoustic, and lexical expressions were analysed during memory reminiscence. Results showed that differences exist between the past and present valence. Due to the reappraisal of the memory, a shift in valence occurred as a strong fading effect was seen in the sad memories, while a slight positive bias was also present as the older adults were more biased towards positive emotions in happy memories. Different modalities were more relevant for past than for present valence. These findings show that distinguishing between past and present valence is important when studying emotions in older adults’ memories. Older adults are more biased towards positive emotions and minimize negative emotions. Finally, automatic emotion recognition technology can benefit from these findings to assist older adults in the future.